Uma análise do produto potencial para os estados brasileiros : ciclos e determinantes externos - Cruz, Joelson Junio Azeredo (2017)
The main objective of this work was to make an empirical analysis of the impacts of trade balances and real exchange rate on potential output changes for Brazilian states. It was hypothesized that either external demand shocks or shocks to the real exchange rate cause a change in potential output. As there are no works that have made such tests for the Brazilian states, but only for Brazil as a whole, the main contribution of this study was then to test the endogeneity of potential output to such factors by an expressive number of observations. Thus, by estimating the Brazilian states’ potential output through a specific method, the HP filter, a following Granger causality analysis was performed based on the Dumitrescu and Hurlin (2012) methodology. The findings demonstrated that both real exchange rate and trade balance shocks cause potential output changes in Brazilian states. These evidences corroborate the idea of some Brazilian authors that set the real exchange rate in a central place to stimulate the economic development in Brazil (BRESSER-PEREIRA, 2006; OREIRO, 2012). One way to interpret the results of this work is by separating it into two channels: a) a direct channel, on the supply side, because an increase of the real exchange rate would rise the participation of the industrial sector on the GDP, and consequently pushing up the productivity of the economy as whole; b) an indirect channel, on the demand side, as an increase of the real exchange rate induces higher trade baances and thus increasing potential output in the Brazilian states. Furthermore, Granger causality from real exchange rate to trade balances were confirmed for the Brazilian units by this work.